Poor Oral Health and Pre-Term Low Birth Infants - Bashar, AKM; Alam, MS (Bangladesh Medical Journal, 2009)
Oral health though often considered as a distinct specialty that is separate from the body as a whole, but the health of the oral cavity can have wide-reaching effects on overall health. Poor oral health may occur concomitantly with a more serious underlying disease process or may predispose an individual to other health conditions. This article examines the relationship between poor oral health and increased risk for Pre-term low birth weight infants, underscoring that the oral cavity and its tissues are an integral part of the human body. DOI: 10.3329/bmj.v37i2.3595 Bangladesh Medical Journal 37(2) 2008 56-65